PENERAPAN METODE COOPERATIVE LEARNING TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR DALAM BAHASA INGGRIS PADA KELAS XI BOGA SMK NEGERI 2 PARIAMAN SEMESTER 2 TAHUN PELAJARAN 2016/2017 - Hastati, F. Yan. R. (Ensiklopedia Education Review, 2020)
This type of research is qualitative research as the subject in this study is 37 students of class XI Boga SMKN 2 Pariaman consisting of 36 female students and 1 male student. In conducting this research, researchers examined the implementation of learning by applying the cooperative learning model type Group Investigation. Based on the results of research carried out at SMKN 2 Pariaman in class XI Boga students in the second semester of the 2016/2017 academic year with the application of the Cooperative Learning Model Group Investigation type, it is known that there is an increase in learning outcomes obtained by students in cycle I on average 70.6 to increase in cycle II, the class average score reached 81.84 above the KKM 75